2009
DOI: 10.1177/0044118x09336631
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Adolescents’ Experience of Family Violence and Dating Violence

Abstract: This study examines whether experiences of familial victimization and aggression are potential risk factors for dating violence in male and female teenage relationships. The authors compare 471 adolescents aged 12 to 19 in the care of a youth protection agency and from a community sample. Results show that adolescents carry negative childhood experiences of family violence into their intimate relationships in different ways, depending on gender and level of risk. Female adolescents who had been victimized by e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
0
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 40 publications
4
44
0
8
Order By: Relevance
“…These dynamics are reciprocal and may carry over into other intimate relationships. In another study, we found that the extent of youths' aggression toward their parents was a significant predictor of whether or not they were aggressive toward their dating partners, particularly for girls (Laporte et al 2011). …”
Section: Individual Developmentmentioning
confidence: 82%
“…These dynamics are reciprocal and may carry over into other intimate relationships. In another study, we found that the extent of youths' aggression toward their parents was a significant predictor of whether or not they were aggressive toward their dating partners, particularly for girls (Laporte et al 2011). …”
Section: Individual Developmentmentioning
confidence: 82%
“…Furthermore research by Milletich et al (2010) and Franklin and Kercher (2012) showed that girls witnessing domestic violence and controlling behaviour within the family were more vulnerable to experiences of domestic violence in later life. Boys experiencing similar home circumstances however, were found by Laporte et al (2011) to be more likely to become the perpetrator of violence within their relationships. Alongside studies such as these, there is also research that links aggression to empathic capacity and which show that exposure to violence may actually reduce empathy (Krahé & Möller, 2010).…”
Section: The Normalisation Of Sexual Relations With Childrenmentioning
confidence: 93%
“…One study found that women who had experienced victimization by their family were more likely to be revictimized in their dating relationships during adolescence compared to men (Laporte, Jiang, Pepler, & Chamberland, 2011). Other research corroborates that women are more likely to be revictimized in their relationships in early adulthood compared to men; however, other research also indicated that men are equally at risk for revictimization in other outcome domains (Chan, 2011; Tyler, Johnson, & Brownridge, 2008).…”
Section: Introductionmentioning
confidence: 99%